Advances in enterprise information systems II : proceedings of the fifth International Conference on Research and Practical Issues of Enterprise Information Systems (CONFENIS 2011), Aalborg, Denmark, October 16-18, 2011 /: proceedings of the fifth International Conference on Research and Practical Issues of Enterprise Information Systems (CONFENIS 2011), Aalborg, Denmark, October 16-18, 2011. (©2012) - Unknown
No abstract available